A metabolomics characterisation of natural variation in the resistance of cassava to whitefly - Pérez Fons, Laura; Bohórquez Cháux, Adriana; Irigoyen, Maria L.; Garceau, Danielle C.; Morreel, Kris; Boerjan, Wout; Walling, Linda L.; Becerra López Lavelle, Luis Augusto; Fraser, Paul D. (Springer, 2019)
Abstract Background Cassava whitefly outbreaks were initially reported in East and Central Africa cassava (Manihot esculenta Crantz) growing regions in the 1990’s and have now spread to other geographical locations, becoming a global pest severely affecting farmers and smallholder income. Whiteflies impact plant yield via feeding and vectoring cassava mosaic and brown streak viruses, making roots unsuitable for food or trading. Deployment of virus resistant varieties has had little impact on whitefly populations and therefore development of whitefly resistant varieties is also necessary as part of integrated pest management strategies. Suitable sources of whitefly resistance exist in germplasm collections that require further characterization to facilitate and assist breeding programs.